Differential Impact of Weight Loss and Glycemic Control on Inflammasome Signaling. Issue 3 (5th February 2020) - Antonioli, Luca; Moriconi, Diego; Masi, Stefano; Bottazzo, Dario; Pellegrini, Carolina; Fornai, Matteo; Anselmino, Marco; Ferrannini, Ele; Blandizzi, Corrado; Taddei, Stefano; Nannipieri, Monica
Abstract : Objective: Interleukin (IL)‐1β is involved in obesity‐associated inflammation and in the pathogenesis of type 2 diabetes (T2D) mellitus. Our aim was to correlate serum IL‐1β and caspase‐1 levels with weight loss, glucose metabolism, and insulin resistance (IR) after bariatric surgery. Methods: A total of 32 patients with morbid obesity and T2D (Ob‐T2D) and 29 patients with morbid obesity and normal glucose tolerance (Ob‐NGT), treated by Roux‐en‐Y gastric bypass, were studied before and 1 year after surgery. Sixteen healthy individuals served as a control (HC) group. IR was assessed by the oral glucose insulin sensitivity method. Plasma IL‐1β levels and caspase‐1 were measured. Results: Presurgery BMI was similar in Ob‐NGT and Ob‐T2D. IR was progressively impaired in Ob‐NGT and Ob‐T2D ( P  < 0.0001). Fasting plasma IL‐1β and caspase‐1 levels were lower in HCs than in patients with Ob‐NGT or Ob‐T2D ( P  < 0.02; P  = 0.05), and both were inversely correlated with IR ( P  = 0.01; P  = 0.02). After surgery, BMI decreased and IR improved to a similar extent in Ob‐NGT and Ob‐T2D ( P  < 0.0001). Plasma caspase‐1 concentrations normalized in both groups ( P  < 0.0001), whereas plasma IL‐1β levels normalized only in Ob‐NGT. Conclusions: Plasma IL‐1β and caspase‐1 levels were inversely correlated with IR. Caspase‐1 levels normalized after weight loss, whereas IL‐1β normalized only in people without T2D, suggesting the persistence of a systemic inflammatory condition in people with T2D.